2023
DOI: 10.5455/ovj.2023.v13.i6.7
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity induced by different diameters of sphere gold nanoparticles with special emphasis on the nephroprotective role of quercetin

Abstract: Background: Although, gold nanoparticles (GNPs) are attracting more and more attention due to their ease of synthesis, modification and great potential value in biomedical application, exhibited harmful effects on human health and other living species. Quercetin (Qur) clarify diverse pharmacological effects specially anti-inflammatory, antiapoptotic, and antioxidant ones. Aim: This study aimed to evaluate the probable nephrotoxicity induced by different diameters of sphere GNPs, as well as the nephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(29 reference statements)
1
1
0
Order By: Relevance
“…In addition, they also clarified that Qur prevents the development of hepatic fibrosis and reduces toxicant-induced liver injury. These findings were supported by Abdelrahman et al 51 who noticed that the Qur has more potent cytoprotective, anti-inflammatory, and anti-apoptotic effects and has a significant mitigating role against the GNPs toxicity. And also, the position of Qur was supported by Eldin et al 43 who demonstrated that histopathological effects induced by the metal particle were observed to be mitigated by concurrent Qur administration, as evidenced by a lack of Prussian blue staining in the Qur-treated group.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In addition, they also clarified that Qur prevents the development of hepatic fibrosis and reduces toxicant-induced liver injury. These findings were supported by Abdelrahman et al 51 who noticed that the Qur has more potent cytoprotective, anti-inflammatory, and anti-apoptotic effects and has a significant mitigating role against the GNPs toxicity. And also, the position of Qur was supported by Eldin et al 43 who demonstrated that histopathological effects induced by the metal particle were observed to be mitigated by concurrent Qur administration, as evidenced by a lack of Prussian blue staining in the Qur-treated group.…”
Section: Discussionsupporting
confidence: 58%
“…Finally, the current study clarified that the greatest pathological changes were noticed in G2 received 10 nm GNPs more than other groups that received larger diameters; 20 and 50 nm GNPs. Where, this finding was confirmed by the result of Abdelrahman et al 51 who clarified that the size of GNPs is pivotal in their pathological effect on the renal tissues where the small-sized GNPs, 10 nm have more potent cytotoxic, inflammatory, and apoptotic effects rather than the larger ones.…”
Section: Discussionmentioning
confidence: 66%